Social ties and practices of inclusion and exclusion: Somali response to droughts - Ahmed M. Musa (Danish Institute for International Studies (DIIS), 2023)
Principles of humanity, neutrality, impartiality and independence guide international humanitarian response. Despite being bound to these principles, international humanitarianism faces challenges of implementation within complex and protracted humanitarian crises. The Somali response to emergencies, such as droughts, takes place in parallel with international humanitarianism but it is not guided by such written principles. Also, there is limited understanding of the operations of the Somali response. Drawing on fieldwork in Hargeisa, Burao, Borama and Gargaara in November 2020, this working paper analyses inclusion and exclusion in the Somali drought response. The paper makes two contributions. First, it contributes to the crisis response literature, specifically the burgeoning literature on 'civic humanitarianism'. Second, it examines factors that contribute to exclusion and social mechanisms that mitigate it, arguing that these have direct relevance for discussions on humanitarian practices in areas of protracted and complex crises.
Keywords: 330; Somali drought response; inclusion and exclusion; Somalian humanitarianism